Ovo Fintech Application Analysis Using the System Usability Scale - Dewi, Luh Yuliani Purnama; Abdillah, Leon A. (Jurnal Ilmiah Matrik, 2024)
The advancement of information technology has propelled payment systems from conventional methods to technology-based solutions, such as e-wallets and Financial Technology (Fintech). Fintech, a fusion of technology and financial services, has evolved into an online business model enabling fast and remote transactions. This research discusses the progress of information technology (IT) influencing payment systems, particularly in the realm of Fintech. The primary focus is on the Fintech application OVO and its impact on tenants at the International Plaza (IP) Mall in Palembang. This study employs the System Usability Scale (SUS) to evaluate the Usability of the OVO application, emphasizing aspects like effectiveness, efficiency, and user satisfaction. The research is descriptive and quantitative, with a sample of 50 respondents from Mall IP tenants. Data is collected through SUS questionnaires and analyzed using SPSS. The evaluation indicates that the OVO application has high Usability , with an SUS score of 87.05 (Grade A), signifying an “Excellent” rating. It suggests that the OVO application provides a comfortable user experience, particularly in electronic financial transactions.